Safety of dobutamine stress cardiovascular magnetic resonance in patients with prior coronary artery bypass grafting - Jannick Heins; Janek Salatzki; Anne Köhrer; Andreas Ochs; Lukas D. Weberling; Hauke Hund; Evangelos Giannitsis; Norbert Frey; Dirk Loßnitzer; Florian André; Henning Steen (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Patients with coronary artery bypass grafts (CABG) face an elevated risk of major adverse cardiac events. High-dose dobutamine stress cardiovascular magnetic resonance (DCMR) imaging is a well-established technique to detect hemodynamically significant coronary artery disease. However, there is a lack of data regarding the safety of DCMR in patients with CABG. This study aims to evaluate the safety of DCMR in patients with CABG. Methods: We retrospectively studied patients after CABG who subsequently underwent DCMR between November 2008 and July 2018. Side effects, defined as adverse events and minor symptoms, during DCMR were analyzed and compared to 200 individuals matched for age, sex, and body mass index without prior CABG undergoing DCMR. Results: Three hundred and thirty-six patients (70 ± 9 years, 85% men (284/336)) were identified. Adverse events occurred in 35 CABG patients (10% (35/336)) and 18 controls (9% (18/200), p = 0.595). A drop of systolic blood pressure (SBP) >40 mmHg (12 patients), non-sustained ventricular tachycardia (6 patients), increase in SBP >200 mmHg (5 patients), monomorphic premature ventricular contractions (PVC) (2 patients), bigeminy (2 patients), left bundle-branch block (2 patients), as well as tachycardiac paroxysmal atrial fibrillation, bradycardia, supraventricular tachycardia, couplets/triplets, and sinus arrhythmia in 1 patient each occurred in the study group. In addition, one patient was hospitalized due to tachycardiac paroxysmal atrial fibrillation and transient ischemic attack. Twenty-nine (8.7% (29/336)) examinations in the study group were aborted because of either chest pain, dyspnea, nausea, dizziness, a drop of SBP, arrhythmias, tachycardiac paroxysmal atrial fibrillation, monomorphic PVCs, or non-sustained ventricular tachycardia. The rate of aborted examination was comparable to the control group (7.5% (15/(200), p = 0.631). Univariable logistic regression analysis revealed that female sex (odds ratio [OR] 2.21, 95% confidence intervals [CI] 1.2–4.3, p = 0.017) and inducible ischemia (OR 3.50, 95% CI 2.0–6.0, p < 0.001) were associated with an increased risk of side effects during DCMR. Conclusion: Dobutamine stress CMR did not show a relevant increase in adverse events in patients with prior CABG compared to patients without prior CABG. Female sex and dobutamine-induced myocardial ischemia are associated with side effects during DCMR.